Generation and Validation of Synthetic WDS Case Studies Using Graph Theory and Reliability Indexes. (2017) - Paez, D.; Filion, Y.
Abstract: Finding case studies that give statistical significance to the conclusions of research on Water Distribution Systems (WDS) can be a challenging task. The generation of synthetic (virtual) WDSs has been proposed recently to tackle this difficulty. These methods try to generate realistic data, based on different assumptions for different properties of the networks. This paper describes the use of a method for the generation of synthetic distribution systems and its subsequent comparison against real life systems to validate the suitability of the synthetic set to drive the conclusions of future research. Focus was given to connectivity and reliability-related indexes considering the future use of these synthetic WDSs to study relationships between connectivity, reliability and energy consumption. The algorithm for the generation of synthetic WDSs was based on the work, methods and software presented by Mair et al.[1] . The validation procedure was made by evaluating metrics or indexes that account for network connectivity and system reliability and comparing their ranges in both sets. Early results showed that the synthetic WDSs required an enhancement of network connectivity to make them more similar to real-life systems. After implementing a routine to increase the meshedness of the networks, an acceptable degree of similarity between the synthetic and the real-life sets of WDSs was achieved, although some modifications to the networks may be required in the future.